Pengaruh Hasil Belajar Perpajakan, Intensitas Pemberian Tugas dan Gaya Belajar Terhadap Pemahaman Akuntansi Perpajakan dengan Motivasi Belajar Sebagai Variabel Moderating (Studi Pada Mahasiswa Akuntansi Unisma) - Khoiroh, Annis Duwi Rokhmatul; Diana, Nur; Hidayati, Irma (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to determine the influence of taxation learning outcomes, intensity of assignments, learning style and learning motivation on understanding tax accounting, and the influence of taxation learning outcomes, intensity of assignments and learning style on understanding taxation accounting with learning motivation as a moderating variable. The type of research used is quantitative research with a data collection method, namely a survey method using a questionnaire distributed to students of the Accounting study program at the Islamic University of Malang. The data analysis method used in this research is multiple linear regression analysis using 2 models. Model 1 aims to see the relationship between one dependent variable and more than one independent variable, while Model 2 aims to test the influence of the three independent variables on the dependent variable by including moderating variables. The results of research that has been carried out have found several things, including the following: Taxation learning outcomes; Learning style and learning motivation have a positive and significant effect on understanding tax accounting, while the intensity of assignments does not have a significant effect on understanding tax accounting. Learning motivation weakens the relationship between Tax Learning Outcomes, Intensity of Assignment, and Learning Style on Understanding Tax Accounting.Keywords : Learning outcomes, intensity of assignments, learning style, learning motivation.